Testing the Role of Aspirations, Future Expectations, and Strain on the Development of Problem Behaviors across Young and Middle Adulthood. Issue 12 (2nd December 2017) - Knight, Kelly E.; Ellis, Colter; Roark, Jennifer; Henry, Kimberly L.; Huizinga, David
Abstract: Using prospective data collected across 14 years by the National Youth Survey Family Study ( N = 1, 436), we assessed change in aspirations, future expectations, and strain, as well as contemporaneous and longitudinal effects of these predictors on drug use, offending, and the perpetration of intimate partner violence. Growth curve models showed that, although time significantly predicted change in these variables, trajectories remained relatively stable. Contemporaneous random-intercept regression models revealed that all three measures were associated with all three problem behaviors. The effects were predictive longitudinally but some associations and gender differences were attenuated when controlling for prior involvement in outcomes.